Abnormal Expression of CD54 in Mixed Reactions of Mononuclear Cells from Hyper-IgE Syndrome Patients (2004)
ABSTRACT: Hyper-IgE syndrome (HIES) is a rare multisystem disorder characterized by increased susceptibility to infections associated with heterogeneous immunologic and non-immunologic abnormalities. Most patients consistently exhibit defective antigen-induced-T cell activation, that could be partly due to altered costimulation involving accessory molecules; however, the expression of these molecules has never been documented in HIES. Therefore, we investigated the expression of CD11a, CD28, CD40, CD54, CD80, CD86, and CD154 in peripheral blood mononuclear cells from six patients and six healthy controls by flow cytometry after autologous and mixed allogeneic reactions. Only the allogeneic stimuli induced significant proliferative responses and interleukin 2 and interferon gamma production in both groups. Most accessory molecules showed similar expression between patients and controls with the exception of CD54, being expressed at lower levels in HIES patients regardless of the type of stimulus used. Decreased expression of CD54 could partly explain the deficient T cell activation to specific recall antigens in HIES patients, and might be responsible for their higher susceptibility to infections with defined types of microorganisms.